ETHNIC CONFLICTS IN IRAQI SOCIETY: THE KURDISH- TURKMEN CONFLICT IN KIRKUK AS A MODEL - Sabar, Mohammed Ghazi (PT. Antis International Publisher, 2025)
Objective: This research addresses the issue of ethnic conflicts in Iraqi society by analysing the Kurdish-Turkmen conflict in the city of Kirkuk as a representative example of the complexities of national diversity in Iraq, seeking to explore the historical, social and political dynamics that have shaped this chronic conflict, focusing on the intersection of competing identities with struggles over power and resources, and their impact on the reproduction of tensions between societal components. Method: The research adopts a multidimensional analytical framework based on theories of social identity, realist conflict, and symbolic interaction to explain the mechanisms of ethnic polarisation in Kirkuk. Result: The findings show that the absence of inclusive state institutions, the employment of sub-identities by political elites, and regional interventions have all contributed to perpetuating a state of mutual distrust and marginalisation between Kurds and Turkmen, while also addressing the social, psychological and economic consequences of the conflict, including the disintegration of social networks, the deepening of feelings of identity closure, and the stagnation of development in disputed areas. Novelty: The research concludes with a number of strategic recommendations aimed at enhancing opportunities for peaceful coexistence and effective diversity management, including reforming representative institutions, distributing resources equitably, and promoting an inclusive national identity, drawing on comparative international experiences.